OPTIMIZATION OF ROASTED LINSEED POWDER (RLSP) INCORPORATED CHIDWA LADDU FOOD USING RESPONSE SURFACE METHODOLOGY - S. PARAMESHWARI; P. NAZNI (International Journal of Pharma and Bio Sciences, 2016)
Diet is one of the most important factors that are necessary for the better health of an individual. Provision of diet for the maintenance of physical and mental health is a basic right of an individual and the outcome of factors related to diet on health has been matter of concern since ancient times. Flaxseed (Linum Usitatissimum) is generally cultivated for linen fiber or for oil from its seeds. Flax seed is richest source of alpha-linolenic acid, lignans and other nutritional components. The incorporation of flax seed into diet can help to have a superior taste in regularly consumed dishes. The reddish brown flax seed grains have a pleasant flavour and taste resembling nuts and its utilization is simple in different products. Considering the above facts, this study was undertaken with special interest in the development of omega 3 fatty acid enriched designer food. The aim of the study to optimize roasted linseed powder (RLSP) incorporated Chidwa laddu food using Response Surface Methodology. The optimum condition of rice flakes 138.16g, RLSP 20g, groundnut 28.82g and Bengal gram 20g respectively. Corresponding to these values of process variables, the values of carbohydrate 287.48g, protein 34.39g, omega 3 fatty acid 36.58mg and overall acceptability 8. The overall desirability was 0.51 respectively.